Determination of the position of the N-O function in substituted pyrazine N-oxides by chemometric analysis of carbon-13 nuclear magnetic resonance data - Butler, Matias (2013)
Investigations were carried out app lying NMR spectroscopy for the unambiguous determinatio n of the position of the N-oxide function in a set of 2-substitute d pyrazine N-oxides synthesized in our group. Applying chemometric techniques of multivariate analysis to the 13C NMR chemical shifts data set, useful relationships for identifying the position of the N-oxide group relative to the substituent were unraveled. The relationships obtained were rationalized in terms of the molecular structures and refined. As a result, an index of N-oxidation (INOx) was defined, computed simply contrasting the average 13C NMR chemical shifts of each pair of carbon atoms bonded to a nitrogen atom. The effect of the substituent was included through a factor x (subscript of INO) close to unity, multiplying the average containing the substituted carbon atom. The approach was successful in recognizing the position of the N-oxide in all the cases studied, as revealed by the sign of INOx (positive for 1-N-oxides and negative for 4-N-oxides). The scope of the methodology was further tested using the 13C NMR chemical shifts of disubstituted pyrazine N-oxides from the literature data.